Knowledge about Neonatal Jaundice among Nepalese Mothers - Shrestha, Sharmila; Maharjan, S; Shrestha, S; Petrini, M A (Journal of BP Koirala Institute of Health Sciences, 2019)
Background: Worldwide, Neonatal Jaundice is one of the most common disorders and causes of avoidable brain damage and physical and mental impairment, and probable death in newborns. It is an important contributor to the high neonatal morbidity and mortality in Nepal. Objective: To assess among mothers the knowledge about neonatal jaundice.Method: A descriptive cross-sectional study was conducted among 177 mothers in selected village with convenient sampling technique.Results: Findings revealed that around half of the mothers (49.90%) had low level of knowledge (score 75%) regarding neonatal jaundice. A large proportion of mothers (84%) believed that danger sign of neonatal jaundice was unable to feed the baby. Few 11% mothers believed that mental retardation and death was the complication of neonatal jaundice. Few mothers (12%) were aware about the cause of neonatal jaundice. Around 74% believed that exposing the baby to the sunlight is the primary management of neonatal jaundice but only 2%heard about the phototherapy.Conclusion: Knowledge about neonatal jaundice was low among Nepalese mothers. Awareness should be created among the expecting mothers about neonatal jaundice and encourage them to take preventive measures to avert neonatal mortality and morbidity.